Challenges faced in teaching learning process by the students and teachers during the pandemic: A cross-sectional study (Panacea Journal of Medical Sciences, 2022)
Background: The COVID pandemic has caused drastic changes in education systems in the world. The government enforced the restriction of all the educational institutions all over the country and also throughout the world. Due to shut down of institutions, the mode of learning shifted from on-site, in person learning to online, virtual mode. Thanks to the advancement of the technology and sciences, we were able to connect students to their professional world virtually. The study intends to acknowledge the student’s mentality while attending online classroom and also highlighting the challenges faced due to the online education.Materials and Methods: The study was based on descriptive cross-sectional study and conducted through consented online survey where forms were distributed via social media. A total of 320 participants consented for the survey and willingly participated for it.Results: The survey showed that though the online mode of study was helpful in keeping up with the education, barriers can lead to obstruction for the fluidity of education.Conclusion: We should come up with more innovative ideas to connect students and professors with minimal barriers between them.